أدب الحيوان في مؤلفات العلامة الإلوري: دراسة تحليلية نقدية - Khalil Mohammad Usman Gbodofu (Nady Al-Adab : Jurnal Bahasa Arab, 2020)
الـملخـصيتكون الكون من عدة عوالم، عالم الإنسان، وعالم الحيوان، وعالم النبات، وعالم الجماد. والحيوان كالإنسان يتصف بالحياة والحس، ويمتاز بالتوالد والتناسل، ويتنوع إلى أنواع مختلفة، منها من يمشي على بطنه كالحية، ومنها من يمشي على رجلين كالطيور، ومنها من يمشي على أربع كالأنعام. والعلماء العرب وغير العرب ما زالوا يأخذون في التأليف حول الحيوان، منهم من أفرد له تأليفا مستقلا، ومنهم من لم يفرد له. ومن هؤلاء العلماء الشيخ آدم عبد الله الإلوري الذي كان يناقش شؤون الحيوانات وخصائصها في بعض مؤلفاته، وذلك في أمثال كتاب الإسلام والتقاليد الجاهلية، ونسيم الصبا، ومؤجز تاريخ نيجيريا، وفلسفة النبوة والأنبياء، والجغرافيا والتاريخ. فانطلاقا من ذلك تسهم هذه المقالة في دراسة الحيوانات لدى العلامة الإلوري؛ حيث تبحث عن المصادر التي يعتمد عليها الإلوري، وتسلط الأضواء على موقفه إزاء العلاقة بين الإنسان والحيوان، وتتحدث عن مميزات الحيوانات وبناء القصة حولها، والباحث في هذه المقالة سيقوم بدراسة أدبية محضة من حيث النقد التحليلي. Abstract The universe comprises of many world thus, the world of human being, animals, plants and non-living things. Animals are similar to human being, they both share life, feeling and distinct other creatures with rotation and reproduction. They are in different species. Some of them walk on their stomach such as snakes, including those who walk with two legs such as birds and including those who walk with four legs such as cattle.Many Arab and non-Arab scholars have written on animals. Some among these scholars single handedly wrote on animals while some did not. Among those scholars are Sheikh Adam Al-Ilory who elaborates on the attitude and characteristics of animals in some of his works which includes; “Islam and Customs of the dark age”, “Breeze of Dawn”, “Summary History of Nigeria”, Philosophy of Prophet-hood and the Prophets” and “Geography and History”.This paper therefore, study al-Ilory perspectives on animals, the sources explored by al-Ilory in his submission and shed more light on his position between human being and animal. It also discusses the characteristics of animals and it builds a story among them. In this paper, the researcher will carry out a purely literary study in terms of analytical criticism.